2017
DOI: 10.1002/marc.201700561
|View full text |Cite
|
Sign up to set email alerts
|

Copper(0) Mediated Single Electron Transfer Controlled Radical Polymerization toward CF Bonds on Poly(vinylidene fluoride)

Abstract: The first copper(0) mediated controlled radical polymerization (CRP) of methyl methacrylate (MMA) toward CF bonds onto poly(vinylidene fluoride) (PVDF) is reported with rather high activity. By avoiding the halogen exchange, Cu instead of Cu complexes utilized as catalyst is responsible for the significantly improved polymerization activity. Using FH decoupled nuclear magnetic resonance technique, the grafting sites onto PVDF are finely located. From this, detailed topologic information including the graftin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Recent finding indicates that the utilization of F−H decoupled 1 H NMR can detect slight alterations in chemical shifts and confirm the activation sites in PVDF-based graft copolymers, as detailed in our previous report. 22 To further elucidate the initiating sites associated with C−F bond activation, F−H decoupled 1 H NMR of the graft copolymer was performed and compared with that prepared with Cu(0)/ Bpy complexes, as depicted in Figure 2b. In addition to the typical signals of VDF units and residual solvent peaks, a distinctive signal at 2.82 ppm is observed in the graft copolymer prepared with the Cu(0)/Bpy complex.…”
Section: Synthesis and Characterization Of The Graftmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent finding indicates that the utilization of F−H decoupled 1 H NMR can detect slight alterations in chemical shifts and confirm the activation sites in PVDF-based graft copolymers, as detailed in our previous report. 22 To further elucidate the initiating sites associated with C−F bond activation, F−H decoupled 1 H NMR of the graft copolymer was performed and compared with that prepared with Cu(0)/ Bpy complexes, as depicted in Figure 2b. In addition to the typical signals of VDF units and residual solvent peaks, a distinctive signal at 2.82 ppm is observed in the graft copolymer prepared with the Cu(0)/Bpy complex.…”
Section: Synthesis and Characterization Of The Graftmentioning
confidence: 99%
“…To avoid the halogen exchange reaction that arises from mixed halogen species in the reaction system, our group first reported Cu(0)-mediated single electron transfer controlled radical polymerization (SET-CRP) for grafting modification of PVDF. 22 The activating sites in the graft copolymer were confirmed through careful characterization of its chemical structure. Furthermore, the reactivity of the C−F bond in PVDF-based fluoropolymers is closely linked to their chemical structure, which subsequently impacts the grafting efficiency.…”
Section: Introductionmentioning
confidence: 95%
“…At present, the only effective catalytic system for activating C-F bonds to prepare PVDF-based graft copolymers is copper complexes. [18][19][20][21] However, the side reaction of dehydrofluorination (𝛽-H elimination) inevitably occurs when the copper complex is used as the catalyst, which has been reported in Cu(0)-mediated single electron transfer controlled radical polymerization (SET-CRP). [22][23][24] In fact, Cu-induced catalytic radical termination is a non-negligible reason for the loss of chain-end functionality in traditional Cu-mediated ATRP, involving a 𝛽-H elimination to form an unsaturated polymer chain.…”
Section: Doi: 101002/macp202200041mentioning
confidence: 99%
“…Besides ATRP strategy, Zhang et al [214] reported the grafting of PMMA onto PVDF by single electron transfer-controlled radical polymerization (SET-CRP) toward C-F bonds catalyzed with Cu 0 and bipyridine (bpy). In the absence of halogen exchange, Cu 0 showed significantly improved catalytic activity than Cu I complexes based typical ATRP system.…”
Section: Graft Copolymers Via Raft/madix Polymerizationmentioning
confidence: 99%